The Civil War in southern Appalachian Methodism - Dunn, Durwood, 1943- (University of Tennessee Press, 2013)
The Civil War in Southern Appalachian Methodism addresses a much-neglected topic in both Appalachian and Civil War history-the role of organized religion in the sectional strife and the war itself. Meticulously researched, well written, and full of fresh facts, this new book brings an original perspective to the study of the conflict and the region. In many important respects, the actual Civil War that began in 1861 unveiled an internal civil war within the Holston Conference of the Methodist Episcopal Church, South-comprising churches in southwestern Virginia, eastern Tennessee, western No.